Selective Policy in Handling Illegal Immigrants - Kristofel Aditya Prathama Pardamean Hutauruk; Ahmad Redi; Suparno Suparno (CV. Publikasi Indonesia, 2023)
The weak legal position of the Indonesian state in tackling the problem of illegal immigrants has resulted in the Indonesian state no longer being a transit country for illegal immigrants from the Middle East to Australia but has become a destination country because the people in Indonesia are known to be friendly and welcoming in dealing with illegal immigrants who later became destination countries with the target of seeking political asylum, human smuggling agents deliberately made Indonesia a destination country for people smuggling. Various efforts have been made by obligated parties, such as the Police institution. The steps taken by the National Police so far have been to arrest illegal immigrants and smugglers, but the investigation process does not use the Special Law, but the Migration Law, so the results obtained do not show significant changes. After Indonesia's independence, Indonesia did not implement the previous policy, namely the